Value Assumptions in Risk Assessment A Case Study of the Alachlor Controversy - Brunk, Conrad G.; Brunk, Conrad G.; Haworth, Lawrence; Lee, Brenda (Wilfrid Laurier University Press, 2006)
Selected by Choice as one of the outstanding publications for 1991. Are risk debates disputes between those who accept the findings of science and those who do not? Between good and bad science? Or is it possible that opposing assessments of risk, by scientific experts as well as ordinary citizens, reflect and are guided by dominant values held by the assessors? The following analysis of one of these debates supports the latter view. In it we suggest what those dominant values are, how they work within a risk assessment, and some implications of reconceiving risk debates as primarily debates about values.